COMPONENT COMPOSITION OF THE BODY OF ARMRESTLERS OF VARIOUS LEVEL OF PREPAREDNESS - Nikulin, I.N.; Maksimenko, V.A.; Possokhov, A.V.; Sobyanin, F.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the features of the somatotype of athletes - armwrestlers of various qualifications. Methods and structure of the study. The experiment was carried out during the preparation of athletes for the All-Russian competitions in arm wrestling among students at the Belgorod State National Research University. The study involved 30 athletes of various qualifications involved in arm wrestling. Respondents were conditionally divided into two groups: qualified athletes with the category of Candidate Master of Sports (CMS) and above (n=15), and athletes of mass categories and without categories (n=15). Fat mass, percentage of fat mass relative to total weight, percentage of active cell mass and skeletal muscle mass relative to lean mass, as well as the somatotype of athletes were determined. To determine the somatotype, a 7-point Sheldon rating scale was used. Results and conclusions. As a result of the study of the somatotypes of athletes involved in arm wrestling at the level of mass sports categories, the dominant type of mesomorphy was revealed. The most preferred body type for the effectiveness of the competitive activity of qualified armwrestlers of medium and heavy weight categories (80 kg and more) is endo-mesomorphic. Athletes with a wide range of relative values of body fat mass can demonstrate high sports achievements in arm wrestling.